Class act : the jazz life of choreographer Cholly Atkins - Atkins, Cholly (Columbia University Press, 2001)
Cholly Atkins's career has spanned an extraordinary era of American dance. He began performing during Prohibition and continued his apprenticeship in vaudeville, in nightclubs, and in the army during World War II. With his partner, Honi Coles, Cholly toured the country, performing with such jazz masters as Louis Armstrong, Cab Calloway, and Count Basie. As tap reached a nadir in the fifties, Cholly created the new specialization of ""vocal choreography, "" teaching rhythm-and-blues singers how to perform their music by adding rhythmical dance steps drawn from twentieth-century American dan